Peran Pola Asuh Otoritatif Orang Tua, Pendidikan Orang Tua dan Jumlah Saudara Terhadap Kemandirian Anak - Wasinah, Wasinah (Universitas Ahmad Dahlan, 2015)
This study aims to determine the role of authoritative parenting, parentsâ education, number of siblings toward independence at an early age children in kindergarten IT Salman Al Farisi. This research used quantitative approach with correlation type. The research subject was 53 students of kindergarten IT Salman Al Farisi Yogyakarta. Data collection instruments used in the form of guidelines for observation of independence, authoritative parenting scale, parentsâ education questionnaire, and the questionnaire of siblings numbers. Data analysis techniques used multiple regression. The results showed that there were positive and highly significant role between authoritative parenting, parentsâ education, and number of siblings toward independence together amounted to 39.6%. Specifically there is a positive role and very significant between authoritative parenting towards independence with a contribution of 27.2%, there is a positive role and significant correlation between parentsâ education towards independence with a contribution of 21.2%, there is a positive role and very significant between number of siblings toward independence with contributions 51.6%. The results of this study can be used as information for guidance and counseling teachers in providing information to parents about appropriate parenting for children to make them grow and develop optimally.